An algebra problem by Renz Mina

Algebra Level 3

x x x + x + x + x + 9 = 0 \sqrt{x \sqrt{x \sqrt{x \ldots}}} + \sqrt{x + \sqrt{x + \sqrt{x + \ldots}}} - 9 = 0

Determine the value of x x that satisfies the above equation.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Sai Ram
Aug 18, 2015

Let x x x = a \sqrt{x \sqrt{x \sqrt{x \ldots}}} = a and x + x + x + = b . \sqrt{x + \sqrt{x + \sqrt{x + \ldots}}} = b.

Now a 2 = x × a a = x . a^2 = x \times a \Rightarrow a=x.

Now, b 2 = x + b b = 1 + 1 + 4 x 2 . b^2=x+b \Rightarrow b = \dfrac{1+\sqrt{1+4x}}{2}.

x x x + x + x + x + = a + b = 9. \sqrt{x \sqrt{x \sqrt{x \ldots}}} + \sqrt{x + \sqrt{x + \sqrt{x + \ldots}}} = a+b =9.

Therefore ,

a + b = x + 1 + 1 + 4 x 2 = 9 x = 6. a+b = x+\dfrac{1+\sqrt{1+4x}}{2} = 9 \Rightarrow x=6.

Hope everyone likes my solution.

Nice solution Sai Ram.. Did the same way :)

Jun Arro Estrella - 5 years, 9 months ago

Log in to reply

Thanks for the compliment : ) :)

Sai Ram - 5 years, 9 months ago

Let X = x x x . . . X=\sqrt{x\cdot \sqrt{x \cdot \sqrt{x \cdot ... }}} and Y = x + x + x + . . . Y=\sqrt{x+ \sqrt{x + \sqrt{x + ... }}} . We have, in the first place, that

X 2 = x X X = x X^2=x \cdot X \implies X=x

and, in the second place, that

Y 2 = x + Y Y = 1 + 1 + 4 x 2 Y^2=x+Y \implies Y=\displaystyle\frac{1+\sqrt{1+4x}}{2}

So, we can conclude that

x x x . . . + x + x + x + . . . 9 = 0 \sqrt{x\cdot \sqrt{x \cdot \sqrt{x \cdot ... }}}+\sqrt{x+ \sqrt{x + \sqrt{x + ... }}}-9=0 \implies x + 1 + 1 + 4 x 2 = 9 x = 6 x+\displaystyle\frac{1+\sqrt{1+4x}}{2}=9 \implies x=6

Ben Habeahan
Aug 30, 2015

x x x . . . + x + x + x + . . . 9 = 0 \sqrt{x{ \sqrt{x{\sqrt{x ...}}}}}+\sqrt{x{+ \sqrt{x+\sqrt{x +...}}}}-9=0 x 1 2 + 1 4 + 1 8 + . . . + x + x + x + . . . 9 = 0 x^{ \frac{1}{2}+ \frac{1}{4}+ \frac{1}{8}+...}+\sqrt{x{+ \sqrt{x +\sqrt{x +...}}}}-9=0

x 1 2 1 1 2 + x + x + x + . . . 9 = 0 x^ \frac{{ \frac{1}{2}}}{{1-\frac{1}{2}}}+\sqrt{x{+ \sqrt{x +\sqrt{x +...}}}}-9=0 x + x + x + . . . = 9 x ( ) \sqrt{x{+ \sqrt{x +\sqrt{x +...}}}}=9-x (*)

Square ( ) (*) it, x + x + x + x + . . . = ( 9 x ) 2 ( ) x{+ \sqrt{x+\sqrt{x +\sqrt{x +...}}}}={(9-x )}^2(**) (with x < 9 ) . x<9 ). Subtitution ( ) (*) to ( ) (**) we can have x + ( 9 x ) = ( 9 x ) 2 x = 6 x+(9-x)={(9-x)}^2 \implies x=6 (because x = 12 > 9 ) . x=12>9).

x = 6 x= \boxed6

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...